MODERATING ROLE OF MARKET SHARE AND FINANCIAL HEALTH ON REAL EARNINGS MANAGEMENT AND COST EQUITY - Mumpuni Wahyudiarti Sitoresmi; Alex Johanes Simamora; Agustina Prativi Nugraheni (Buletin Studi Ekonomi, 2025)
This study looks at how market share and financial influence the connection between real earnings (REM) and cost of equity. It focuses manufacturing companies that are listed on the Indonesian Stock Exchange using data 2019 to 2021 as its research sample. REM is evaluated with a combination of abnormal CFO, low productivity, and abnormal discretionary cost, while cost of equity is measured with the Ohslon model. All findings from the regression analysis indicate that the presence of a collaborative business agreement and monetary support diminish the advantageous impact of REM on the equity cost. This suggest that REM could be a sign of competitive advantage, signaling a stable economy and better financial condition, thus reducing the cost of euit. In addition, the study shows that REM often shows information about the market situation through oversold activity, whereas all REM activities share information about financial health including oversold, overproduction, and identified abatement costs. This study contributes to the understanding of REM as an indicator of joint venture and financial health that can help reduce the cost of equity.